Dual stator dynamics in the Shewanella oneidensis MR‐1 flagellar motor. Issue 5 (31st March 2015) - Paulick, Anja; Delalez, Nicolas J.; Brenzinger, Susanne; Steel, Bradley C.; Berry, Richard M.; Armitage, Judith P.; Thormann, Kai M.
Summary The bacterial flagellar motor is an intricate nanomachine which converts ion gradients into rotational movement. Torque is created by ion‐dependent stator complexes which surround the rotor in a ring. Shewanella oneidensis MR‐1 expresses two distinct types of stator units: the Na+‐dependent PomA4B2 and the H+‐dependent MotA4B2. Here, we have explored the stator unit dynamics in the MR‐1 flagellar system by using mCherry‐labeled PomAB and MotAB units. We observed a total of between 7 and 11 stator units in each flagellar motor. Both types of stator units exchanged between motors and a pool of stator complexes in the membrane, and the exchange rate of MotAB, but not of PomAB, units was dependent on the environmental Na+‐levels. In 200 mM Na+, the numbers of PomAB and MotAB units in wild‐type motors was determined to be about 7:2 (PomAB:MotAB), shifting to about 6:5 without Na+. Significantly, the average swimming speed of MR‐1 cells at low Na+ conditions was increased in the presence of MotAB. These data strongly indicate that the S. oneidensis flagellar motors simultaneously use H+ and Na+ driven stators in a configuration governed by MotAB incorporation efficiency in response to environmental Na+ levels.